COMPARATIVE PATHOLOGICAL CHARACTERISTICS OF PLACENTA AT ANTENATAL AND LIVE BIRTH OF FULL-TERM FETUSES - Евгений Леонидович Казачков; Элла Алексеевна Казачкова; Анна Валерьевна Чижовская; Юрий Алексеевич Семенов (The Publishing House Medicine and Enlightenment, 2024)
Due to the development of obstetric and neonatal care, the perinatal mortality rate is gradually decreasing both in the Russian Federation and worldwide. This trend is due to a decline in early neonatal mortality, while the stillbirth rate is becoming a priority by gradually increasing its contribution to perinatal mortality. Despite of development of modern methods of prenatal diagnosis, assessment of biochemical markers of complications of pregnancy, routing of high-risk patients to an expert ultrasonography the problem of antenatal fetal death is not yet conclusive. In developed countries, the rate of stillbirths due to unknown causes is as high as 60% and in the Russian Federation 4.7%. The most common problem in determining thanatogenesis of the case of antenatal fetal death during pregnancy. The aim of the research - compare the pathological features of the placenta at antenatal fetal death and live birth in the outcome of a timely birth using histological and immunohistochemical examination. Materials and methods. The study includes 60 women whose pregnancy was completed in full term of pregnancy (37 weeks 0 days - 41 weeks 6 days). 1 group - patients with antenatal fetal death (n = 30), 2 group - women having a live birth in the outcome of pregnancy (n = 30). A comparative histological and immunohistochemical study of the placenta with determination of the level of expression of GLUT1, HIF-1α and CASP-3 markers was conducted. Results. Mostly antenatal death of the full-term fetus was accompanied by signs of chronic placental insufficiency and hypoxic damage to the stromal-vascular placental part. There has been a statistically significant decrease in GLUT-1 expression and an increase in HIF-1α and CASP-3 expression in placenta of patients with antenatal fetal death in full-term pregnancy. Conclusion. Therefore, the disruption of placenta's energy function, more pronounced processes of apoptosis and hypoxic tissue damage in patients with antenatal death of full-term fetus correlate with histological signs of chronic placental insufficiency and changes in stromal-vascular tract in patients with antenatal full-term fetal death. Further research into placental abnormalities is needed to prevent adverse outcomes of pregnancy.